EXPLORING TEACHERS' EXPERIENCES IN MANAGING CLASSES THROUGH AN INCLUSIVE APPROACH IN ELEMENTARY SCHOOLS - Rossa Lina (Adisam Publisher, 2024)
This literature research aims to explore teachers' experiences in managing classes in elementary schools through an inclusive approach. Inclusive education is an approach that involves all students, including those with special needs, to learn together in a supportive and non-discriminatory environment. Through qualitative research methods, in-depth interviews were conducted with a number of teachers to explore the challenges they faced, the strategies they used, and the impact of an inclusive approach on the teaching and learning process. The research results indicate that the implementation of inclusive education requires adaptation of teaching methods, development of additional competencies for teachers, as well as adequate support both in terms of resources and school policies. Despite the challenges, teachers demonstrate that with appropriate training and good collaboration, inclusive approaches can be implemented effectively. These findings provide practical and theoretical contributions, as well as offering recommendations for improving policies and teacher training programs, to support the creation of a more equitable and supportive learning environment for all students without exception.